Desirable Characteristics of Thailand 4.0 Era School Administrators under Secondary Educational Service Area Office 1, Bangkok Metropolitan - Sonmanee, PhraMaha Watcharapong; Jasuwan , Sansanee (The Journal of Development Administration Research, 2020)
The objectives of this study are as follows: 1) to study the desirable characteristics of Thailand 4.0 era school administrators, 2) to study the qualifications of administrators in secondary schools in Thailand 4.0 era. The study used mixed-method research, the samples of this study consist of 9 scholars with administrative and Thailand 4.0 economic model experience as well as 400 secondary school administrators and instructors under secondary educational service area office 1, Bangkok metropolitan. The data was collected by means of oral interviews and questionnaires with 5-Likert rating scales. The statistics employed in this research are frequency, percentage and standard deviation. The factor analysis is the maximum likelihood method and the content analysis method. The results of this research indicate that 1) the desirable characteristics of Thailand 4.0 era school administrators under Secondary Educational Service Area Office 1, Bangkok Metropolitan are 1. decision-making skills 2. competence in motivating people 3. responsibility 4. intelligence and competence 5. personality. 2) The variations in the desirable characteristics of school administrators are: 1. decision-making skills with 6 variations, weighing .417-.75. 2.competence in motivating people with 12 variations, weighing .340-.650. 3.responsibility with 9 variations, weighing .367-.668. 4.intelligence and competence with 16 variations, weighing .369-.783. And 5. personality with 9 variations, weighing .458-.630